2021
DOI: 10.3390/met11101585
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Cu(II), Fe(III), Zn(II), and Mn(II) from Aqueous Solutions with Ionic Liquid R4NCy

Abstract: The leaching of copper ores produces a rich solution with metal interferences. In this context, Fe(III), Zn(II), and Mn(II) are three metals contained in industrial copper-rich solutions in high quantities and eventually can be co-extracted with the copper. The purpose of the current study was to determine the feasibly of solvent extraction with the use of ionic liquid methyltrioctyl/decylammonium bis (2,4,4-trimethylpentyl)phosphinate (R4NCy) as an extractant of Cu(II) in the presence of Fe(III), Zn(II), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…It is essential to note the high selectivity of the ionic liquid for iron and zinc over copper and manganese. This fact can be explained based on previous results [46]. The extraction of the individual elements clearly showed that the performance was more efficient for the extraction of iron and zinc than for copper and manganese under all the conditions under study.…”
Section: Effect Of the R 4 Ncy Concentration In Metal Ions Extractionsupporting
confidence: 70%
See 3 more Smart Citations
“…It is essential to note the high selectivity of the ionic liquid for iron and zinc over copper and manganese. This fact can be explained based on previous results [46]. The extraction of the individual elements clearly showed that the performance was more efficient for the extraction of iron and zinc than for copper and manganese under all the conditions under study.…”
Section: Effect Of the R 4 Ncy Concentration In Metal Ions Extractionsupporting
confidence: 70%
“…The mechanism of metal extraction with R 4 NCy was reported in previous work [46] and can be generalized to all metals in this study, as shown below.…”
Section: Effect Of the R 4 Ncy Concentration In Metal Ions Extractionmentioning
confidence: 76%
See 2 more Smart Citations
“…In(III) can be extracted by ionic liquids, such as n -hexyl-trimethyl ammonium bis(trifluoromethyl-sulfonyl)amide and A327H Cl (by reaction of tertiary amine A327 and HCl) [ 18 ]. The ionic liquid, methyltrioctyl/decylammonium bis 2,4,4-(trimethylpentyl)phosphinate extracted Fe(II) and Zn(II) selectively from a solution containing Cu(II), Fe(II), Mn(II), and Zn(II) [ 19 ]. Another ionic liquid, tetrahexylammonium dicyanamide, has exhibited selective extraction for Cu(II) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%